Zeolite on Arsenic Toxicity Biochemical and Histochemical Study in Fresh Water Fish: Effects of Zeolite on Arsenic Toxicity in Fresh Water Fish: A Biochemical and Histochemical Study (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Zeolites are crystalline strong structure made of silicon, aluminum and oxygen that structure a system with holes and channels inside where water, alerts, as well as little particles may live. They are regularly alluded to as atomic sifters, a considerable lot of which happen normally as minerals. They are mined in numerous pieces of the world and have applications in industry and prescription. Anyway the greater part of the Zeolites have been made artificially, some of them for business use, while others made by researcher to ponder their science. At present, around 191 one of a kind zeolites systems are distinguished.